Predicting perceptions of crime: Community residents’ recognition and classification of local crime problems - Schaefer, Lacey (The Australian and New Zealand journal of criminology, 2018)
In the scholarship of crime prevention, little is understood regarding the prompts for individual observation and classification of local crime problems. Moreover, studies that evaluate individuals’ perceptions of crime tend to emphasise the risk of victimisation rather than the probability of crime controller behaviour. In order to predict whether and how a community resident combats neighbourhood crime and disorder, we first require a greater understanding of how individuals recognise and categorise those same neighbourhood phenomena. To explore these processes, the current project uses large-scale multilevel survey data from the Australian Community Capacity Study to test the predictive influence of individual characteristics, local social processes, and suburb features on a resident’s identification and categorisation of minor, moderate, and major neighbourhood crime problems. Results indicate that lived experiences with prior victimisation and interactions with the police, greater frequencies of neighbouring behaviours but lower levels of collective efficacy, socioeconomic disadvantage, and ethnic homogeneity are all associated with a greater likelihood of reporting serious local crime problems.